2002
DOI: 10.1111/j.1749-6632.2002.tb02099.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment of Rats Caused by Oxidative Stress and Aging, and Its Prevention by Vitamin E

Abstract: In order to verify whether brain damage caused by chronic oxidative stress induces the impairment of cognitive function, the ability of learning and memory was assessed using the water maze and the eight-arm radial maze tasks. Young rats showed significantly greater learning ability before the stress than the old and vitamin E-deficient rats. At five days after subjection to oxidative stress, the memory function of the young declined toward the level of that in the aged rats maintained under normal condition. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
132
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(147 citation statements)
references
References 8 publications
7
132
1
2
Order By: Relevance
“…The fact that acute application of vitamin C and trolox in vitro could not reverse aging-associated impairment of NMDAR-dependent LTP in rat hippocampus in this study suggests that administration of antioxidants, which can reduce ROS generation but not reverse oxidative inactivation of key functional macromolecules directly, has little acute effect on aging-related deficits in synaptic plasticity. In fact, most of the previous studies have indicated that chronic administration of antioxidants for a longer period of time could attenuate aging-related cognitive disorders (Clausen et al;Fukui et al, 2002;Head, 2009), suggesting that antioxidants might have a beneficial effect against brain aging if administered chronically. Considering the accumulation of oxidative damage as a long-term and continuous process, the protection of antioxidants by scavenging ROS might be a long-time result and preventive effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that acute application of vitamin C and trolox in vitro could not reverse aging-associated impairment of NMDAR-dependent LTP in rat hippocampus in this study suggests that administration of antioxidants, which can reduce ROS generation but not reverse oxidative inactivation of key functional macromolecules directly, has little acute effect on aging-related deficits in synaptic plasticity. In fact, most of the previous studies have indicated that chronic administration of antioxidants for a longer period of time could attenuate aging-related cognitive disorders (Clausen et al;Fukui et al, 2002;Head, 2009), suggesting that antioxidants might have a beneficial effect against brain aging if administered chronically. Considering the accumulation of oxidative damage as a long-term and continuous process, the protection of antioxidants by scavenging ROS might be a long-time result and preventive effect.…”
Section: Discussionmentioning
confidence: 99%
“…6C,D), suggesting that the difference may be attributed to the reduction of protein-bound thiol oxidation, not the scavenging of oxygen free radicals. Previous studies have illuminated that chronic administration of antioxidants could attenuate aging-related cognitive disorders (Clausen et al ;Fukui et al, 2002;Head, 2009). However, this study did not show any acute effect of antioxidants on LTP impairment of aged rats.…”
Section: Antioxidant Prevents But Reductant Reverses H 2 O 2 -Inducementioning
confidence: 99%
“…These abnormalities are also observed in both old rats and vitamin E-deficient young rats not subjected to oxidative stress [9]. Morphological changes in the brain caused by oxidative stress have shown that, in rats subjected to hyperoxia, synaptic vesicles containing neurotransmitters abnormally accumulate in nerve terminals, resulting in a marked reduction in the level of acetylcholine released from synapses [10].…”
Section: Introductionmentioning
confidence: 81%
“…ROS generated by chronic oxidative stress which is experienced over a long period may attack the brain, leading to aging and neurodegeneration [20]. In fact, young rats subjected to hyperoxia as oxidative stress and normal aged rats show an increase in the amount of denatured lipids at nerve terminals that is, TBARS and conjugated diene [2], accumulation of amyloid β in the hippocampus, and neuron apoptosis, resulting in deficit in cognition [9,21]. Thus, reactive products of lipid peroxidation have been considered for long time to be a causal factor of neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, it was shown that free O 2 radicals increased in diabetic rat brains, and these increased O 2 -free radicals were decreased using an ET-1 antagonist [57]. Long-term oxidative damage leads to morphological damage and memory disorders in many parts of the brain [58,59], and one previous study showed that diabetes-induced hippocampal neuron damage was prevented by antioxidant therapy [60]. As an indicator of lipid peroxidation and oxidative stress, MDA levels were found to be quite high in the diabetic rats.…”
Section: Discussionmentioning
confidence: 99%